The Relationship between Resilience and Overthinking in Adolescents - Situmorang, Bonita Audina; Widodo, Yohanes Heri (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
The aim of this research is to 1) Find out whether there is a relationship between resilience and overthinking in adolescents. 2) See how high the level of resilience is in adolescents. 3) See how high the level of overthinking is in adolescents. 4) Find out which resilience level scale items are identified as not optimal or low; which can be proposed as guidance topics. 5) Find out which overthinking scale items are identified as not optimal or high; which can be proposed as a guidance topic. This research method is quantitative correlational research. This research was aimed at adolescents at Charitas Jakarta High School. The respondents in this study were 218 adolescents. The measuring instruments used are surveys and data collection instruments for two variables, namely the resilience and overthinking. Items are declared valid with the validity coefficient value, namely r ≥ 0.30 and p value 0.05, and the item is declared reliable when the reliability coefficient is greater than 0.70 (r1 0.70). The results of this study prove that: 1) There is a negative relationship with a high level of significance because the Pearson's r value is -0.688 and p .001. 2) The level of resilience possessed by young students at Charitas Jakarta High School is classified as moderate and tends to be high. This is shown by a total of 218 respondents or adolescents who answered the questionnaire. It shows that there are 134 adolescents indicated to be at a moderate level of resilience, 49 others are at a high level of resilience and 6 adolescents are indicated to have very high resilience. 3) The level of overthinking among adolescents is in the medium position. This is proven by a total of 218 adolescents or 48.17% of respondents who are at the level of medium overthinking tends to be low. 4) The items from the resilience variable that were indicated to be low were found and 4 guidance themes were proposed. 5) The items from the overthinking variables that were indicated as high were obtained and 3 guidance topics were proposed.